A Relationship Between Attitudes, Behaviors, and Knowledge of Preconception Nutrition Among Women Reproductive Age - wati, Aria; Saimin, Juminten; Nasruddin, Nina Indriyani (Faculty of Medicine, Universitas Mataram, 2025)
Background. According to data from the Indonesian Ministry of Health in 2018, a significant proportion of women of reproductive age (15–24 years) in Indonesia experience nutritional deficiencies, particularly Chronic Energy Deficiency (CED), with prevalence rates of 36.3% among non-pregnant women and 33.5% among pregnant women. These findings highlight that non-pregnant women are at a higher risk of CED. This study aims to examine the relationship between attitudes and behaviors of women of reproductive age and their knowledge of preconception nutrition in Anduonohu Village. Method. This observational analytic study utilized a cross-sectional design and was conducted in Anduonohu Village. A total of 97 respondents were recruited using purposive sampling. The dependent variable in this study was knowledge of preconception nutrition, while the independent variables were attitudes and behaviors. Data were analyzed using chi-square tests and logistic regression, with a significance level set at p<0.05. Results.Bivariate analysis demonstrated a significant relationship between attitudes and knowledge of preconception nutrition (p=0.000) as well as between behaviors and knowledge of preconception nutrition (p=0.030). Multivariate analysis further confirmed a significant association between attitudes and behaviors of women of reproductive age and their knowledge of preconception nutrition (p=0.000). Conclusion. There is a significant relationship between the attitudes and behaviors of women of reproductive age and their knowledge of preconception nutrition in Anduonohu Village. Keywords: women of reproductive age, attitude, behavior, knowledge, preconception nutrition Latar Belakang. Berdasarkan data Kemenkes RI tahun 2018, di Indonesia masih banyak wanita usia subur usia 15-24 tahun yang mengalami masalah gizi seperti kekurangan energi kronis sebanyak 36,3% pada WUS tidak hamil dan 33,5% pada WUS hamil, dimana menurut data tersebut lebih banyak WUS yang tidak hamil mengalami kekurangan energi kronis. Penelitian ini bertujuan untuk mengetahui hubungan sikap dan perilaku wanita usia subur terhadap pengetahuan tentang gizi prakonsepsi di Wilayah Kelurahan Anduonohu. Metode. Penelitian ini dilakukan dengan metode analitik observasional dengan menggunakan pendekatan cross sectional yang dilakukan di Wilayah Kelurahan Anduonohu dengan jumlah sampel sebanyak 97 responden. Variabel terikat pada penelitian ini adalah pengetahuan dan variable bebasnya adalah sikap dan perilaku. Data dikumpulkan dengan teknik purposive sampling dan dianalisis menggunakan uji chi square dan regresi logistic ganda dengan nilai signifikan p<0,05. Hasil. Analisis bivariat penelitian menunjukkan bahwa terdapat hubungan yang signifikan antara variabel sikap terhadap pengetahuan dengan nilai p-Value sebesar 0,000 , hubungan yang signifikan antara perilaku terhadap dengan nilai p-Value sebesar 0,030. Pada analisis multivariat terdapat hubungan yang signifikan antara sikap dan perilaku wanita usia subur terhadap gizi prakonsepsi dengan nilai p value sebesar 0,000. Simpulan. Terdapat hubungan antara sikap dan perilaku wanita usia subur terhadap pengetahuan tentang gizi prakonsepsi di Wilayah Kelurahan Anduonohu. Kata kunci: : Wanita Usia Subur, Sikap, Perilaku, Pengetahuan, Gizi Prakonsepsi